Optimal unbiased estimates of P {X < Y} for some families of distributions - Obradović, Marko (Metodološki zvezki, 2014)
In reliability theory, one of the main problems is estimating parameter R = P{X < Y}. In this paper we shall present UMVUEs for R in different cases i.e. for different distributions of X and Y. Some of them are already existing and some are original.
Keywords: Probabilities; Verjetnost (Matematika); Porazdelitev; Distribution; matematična statistika; teorija verjetnosti